2018
DOI: 10.3892/etm.2018.6112
|View full text |Cite
|
Sign up to set email alerts
|

Contrast‑enhanced magnetic resonance imaging with a novel nano‑size contrast agent for the clinical diagnosis of patients with lung cancer

Abstract: Abstract. Recent studies have indicated that magnetic resonance imaging (MRI) efficiently diagnoses lung cancer. However, the efficacy of MRI in diagnosing lung cancer requires improving for patients in the early stage of the disease. In the present study, a novel nano-sized contrast agent of chistosan/Fe 3 O 4 -enclosed bispecific antibodies (BsAbCENS) was introduced, which targeted carcino-embryonic antigen (CEA) and neuron-specific enolase (NSE) in lung cancer cells. The diagnostic efficacy of contrast-enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Contrast agent may increase the sensitivity and accuracy of CT imaging for the diagnosis of early stage NSCLC (23). A novel nano-sized chistosan/Fe 3 O 4 -enclosed bispecific antibody had been identified as an efficient contrast agent in lung cancer diagnosis (40). However, a previous study reported that a nonionic intravenous contrast agent did not cause clinically significant improvement to 18F-FDG PET/CT in patients with lung cancer (41).…”
Section: Discussionmentioning
confidence: 99%
“…Contrast agent may increase the sensitivity and accuracy of CT imaging for the diagnosis of early stage NSCLC (23). A novel nano-sized chistosan/Fe 3 O 4 -enclosed bispecific antibody had been identified as an efficient contrast agent in lung cancer diagnosis (40). However, a previous study reported that a nonionic intravenous contrast agent did not cause clinically significant improvement to 18F-FDG PET/CT in patients with lung cancer (41).…”
Section: Discussionmentioning
confidence: 99%
“…Drug delivery by pulmonary inhalation can be used to treat and diagnose lung diseases; it is a safe, convenient, and non-invasive diagnostic modality. GAO et al [ 340 ] described a novel nano-inhaled contrast agent that can produce a higher signal intensity than MRI alone in diagnosing lung cancer, improving the validity and accuracy of a lung cancer diagnosis. With the application of inorganic NPs as lung delivery carriers, materials based on inorganic plasmonic and magnetic properties can be used to diagnose diseases of the respiratory system, and external magnetic fields, such as positron emission tomography, magnetic resonance imaging, and computed tomography, can direct these magnetic NPs to target sites [ 341 ].…”
Section: Application Of Pulmonary Drug Deliverymentioning
confidence: 99%
“…42 SPIONs (about 130 nm) have been nebulized and delivered to rat lungs, enabling lung imaging with high sensitivity and efficacy via magnetic particle imaging (Fig 4B). 43 Novel nanosized MRI contrast agents developed by Gao et al, 44 chitosan/Fe 3 O 4enclosed bispecific antibodies, were shown to significantly enhance signal intensity for lung cancer after pulmonary inhalation, when compared with MRI alone.…”
Section: Applications Of Intratracheal Delivery Strategymentioning
confidence: 99%